Combined effects of peer presence, social cues, and rewards on cognitive control in adolescents. Issue 3 (1st February 2018) - Breiner, Kaitlyn; Li, Anfei; Cohen, Alexandra O.; Steinberg, Laurence; Bonnie, Richard J.; Scott, Elizabeth S.; Taylor‐Thompson, Kim; Rudolph, Marc D.; Chein, Jason; Richeson, Jennifer A.; Dellarco, Danielle V.; Fair, Damien A.; et al.
Abstract: Developmental scientists have examined the independent effects of peer presence, social cues, and rewards on adolescent decision‐making and cognitive control. Yet, these contextual factors often co‐occur in real world social situations. The current study examined the combined effects of all three factors on cognitive control, and its underlying neural circuitry, using a task to better capture adolescents' real world social interactions. A sample of 176 participants ages 13–25, was scanned while performing an adapted go/no‐go task alone or in the presence of a virtual peer. The task included brief positive social cues and sustained periods of positive arousal. Adolescents showed diminished cognitive control to positive social cues when anticipating a reward in the presence of peers relative to when alone, a pattern not observed in older participants. This behavioral pattern was paralleled by enhanced orbitofrontal activation. The results demonstrate the synergistic impact of social and reward influences on cognitive control in adolescents.